EFFECTS OF HEAT TREATMENT ON THE UPCONVERSION AND NEAR-INFRARED EMISSIONS OF ERBIUM IN TRANSPARENT TELLURITE GLASS-CERAMICS - Vũ Hằng Nga; Đoàn Thị Phúc; Hồ Kim Dân (Tạp chí Khoa học Đại học Đà Lạt)
In this paper, the upconversion (UC) and NIR emissions of Er3+-doped in TeO2–Al2O3–BaF2 (TAB) tellurite transparent glass-ceramics containing BaF2 nanocrystals through the heat treatment process with changing of temperature and duration were investigated.. From the results of X-ray diffraction (XRD) was confirmed that BaF2 nanocrystals have been formed in the TAB glass-ceramics under heat treatment. Through the calculated results from the XRD peaks and transmission electron microscopy (TEM), the crystal size of BaF2 nanocrystals is identified by about 25nm. Compared with the glass samples before heat treatment, UC and NIR emission intensities of Er3+-doped in TAB tellurite transparent glass-ceramics under excitation of 980nm laser diode was significantly increased.